OP28 The effect of guselkumab induction therapy on early clinical outcome measures in patients with Moderately to Severely Active Crohn's Disease: Results from the phase 2 GALAXI 1 study. (27th May 2021) - Danese, S; Sandborn, W J; Feagan, B G; Weisel, K; Gonzalez, S; Frustaci, M E; Yang, Z; Johanns, J; Germinaro, M; Afzali, A; Andrews, J M; D'Haens, G; et al.
Abstract: Background: Guselkumab (GUS), an IL-23 antagonist, is being investigated for the treatment of IBD. GALAXI 1 is a ph2, double-blind, PBO-controlled study in pts with moderately to severely active CD with inadequate response or intolerance to conventional therapies (corticosteroid, immunosuppressant) and/or biologics (TNF antagonist, vedolizumab). Here we report early clinical outcome measures during induction with GUS vs PBO. Methods: Pts with moderate to severe CD (CDAI score 220–450) were randomized 1:1:1:1:1 to GUS 200, 600 or 1200 mg IV at Wks 0, 4, 8; ustekinumab (UST) ~ 6 mg/kg IV at Wk 0 and 90 mg SC at Wk8; or PBO IV. Clinical remission (CDAI score<150), clinical response (≥100-point reduction from baseline in CDAI score or CDAI score<150), and clinical-biomarker response (clinical response and ≥50% reduction from baseline in CRP or fecal calprotectin) were evaluated at Wks 4, 8 and 12 for pooled GUS arms vs PBO. UST was a reference arm. Results: Two hundred fifty pts were evaluated; about 50% failed previous biologic therapy. Baseline demographics and disease characteristics were generally similar among treatment groups (mean CD duration, 8. 8 yr; mean CDAI, 306.2; median CRP, 5. 4 mg/L; median fecal calprotectin, 594. 0 mg/kg). At Wk4, clinical remission was achieved in 20.0% of GUS-treated pts compared with 11.8% of PBO-treated pts. A greater proportion of GUS-treated pts achieved clinical remission compared with PBO-treated pts at Wk8 (42.0% vs 15.7%) and Wk12 (54.0% vs 15.7%). Similarly, within each subgroup of pts who failed biologic therapy(BIO-failures) or conventional therapy(CON-failures), GUS-treated pts achieved a higher rate of clinical remission at Wks 4, 8 and 12 compared with PBO (Fig 1). The proportion of pts who achieved clinical response and clinical-biomarker response was also higher at Wks 4, 8 and 12 among GUS-treated pts compared with PBO-treated pts. From Wks 4 to 8 to 12, the proportion of GUS-treated pts in clinical response increased from 44.0% to 56.0% to 66.0%, respectively, and the proportion in clinical-biomarker response increased from 26.0% to 43.3% to 48.0%. In contrast, the proportion of PBO-treated pts who achieved clinical response and clinical-biomarker response remained stable or decreased from Wks 4 to 8 to 12: 25.5% to 25.5% to 23.5% and 13.7% to 9.8% to 7.8%, respectively (Fig 2). Conclusion: In pts with moderately to severely active CD, induction treatment with GUS combined treatments versus PBO resulted in higher rates of overall clinical remission, clinical-biomarker response, and clinical response as early as Wk4. This continued to increase through Wk12 with treatment. The early trend for achievement of clinical remission was also evident in sub-groups of pts who failed biologic or conventional therapy.